Jam Bel Sekolah Dengan Menghidupkan Speaker Otomatis - Syafi Qurrahman Lubis; Ummul Khair; Arnes Sembiring (SNASTIKOM, 2022)
The bell is a device that can make a sound and has a function as a code, a reminder and a communication tool.In general, in most schools, the operation of the school bell is done manually, i.e. there is a picket teacher orschool officer who must always be ready to ring the school bell according to predetermined hours and inteaching and learning activities at school the school guard / picket teacher is busy with the activity of ringing thebell at school during school hours, changing lessons, taking breaks and going home from school which may bemore than five times a day. But officers often forget to ring the school bell at the right time. This negligencecauses the time taken for lessons which causes the effectiveness of teaching and learning activities to be reduced.So it is still less effective in ringing the school bell according to the hours that have been determined manually.This research builds an automatic bell device that can solve these problems which was built using Arduino Nanoand several other devices with the aim of producing an automatic bell device with bluetooth facilities connectedto a smartphone and applying a bluetooth module to the school bell in managing subject schedules, hours, dates,brightness on the P10 running text module, and turn on the speaker automatically